FORMATION OF STUDENTS' READINESS FOR SELF-MANAGEMENT AS A CURRENT PEDAGOGICAL PROBLEM - L.V. Petŭko (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to revealing of objective and subjective factors of forming of social-communicative activity of teenagers personality in process of touristik activit